The Road to Democratic Backsliding - (:unkn) unknown (My University, 2022)
This dissertation uses three different papers to develop and empirically assess a theoretical framework to explain puzzling support for illiberal incumbents, highlighting the micro-level tradeoffs associated with punishing leaders. I mainly investigate whether affectively polarized regime supporters are more likely to tolerate incumbents who engage in undemocratic action and how affective polarization evolves and why it manifests itself worldwide today. The first paper explores the linkage between democratic backsliding and affective polarization at the country level. The second paper switches its unit of analysis to the individual level and provides direct evidence on the linkage ideological/affective polarization and voters’ willingness to tolerate undemocratic actions. Finally, the third paper shows that affective polarization is also grounded in our social capital. By pro- viding compelling evidence, I have offered new insights concerning the interplay between polarization, social networks, and political behavior on the future of democracy with both substantial theoretical and empirical implications. This project is generously ($15,000) financed by the National Science Foundation Doctoral Dissertation Research Improvement Grant.
Keywords: affective polarization; democratic backsliding; ideological polarization; social capital